1989
DOI: 10.1192/bjp.154.4.516
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Aspects of Hysterectomy

Abstract: Sixty women aged between 30 and 55 years, having hysterectomy for benign conditions, were prospectively studied to investigate psychological adjustment to operation, and to explore social, psychological and physical factors associated with psychological outcome. A further 30 women were included for prospective research on psychological outcome. Investigations took place within two weeks of operation and after four months and 14 months. The findings indicated a high prevalence of pre-operative psychological mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
4
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 17 publications
2
40
4
2
Order By: Relevance
“…Maintaining the ovaries of premenopausal women who have had a hysterectomy may protect against subsequent mood disorder [68,70] although hysterectomy may also cause premature ovarian failure. Being the result of prolonged heavy periods, chronic pelvic pain, and severe MRD, depressed mood is, however, also observed in women before hysterectomy [71][72][73][74]. Hysterectomy may thus improve mood, except for women with preexisting psychiatric illness or predisposing personality problems, in whom depressed mood may persist or re-occur in response to the stress associated with surgery [72,74].…”
Section: Menopausementioning
confidence: 99%
See 1 more Smart Citation
“…Maintaining the ovaries of premenopausal women who have had a hysterectomy may protect against subsequent mood disorder [68,70] although hysterectomy may also cause premature ovarian failure. Being the result of prolonged heavy periods, chronic pelvic pain, and severe MRD, depressed mood is, however, also observed in women before hysterectomy [71][72][73][74]. Hysterectomy may thus improve mood, except for women with preexisting psychiatric illness or predisposing personality problems, in whom depressed mood may persist or re-occur in response to the stress associated with surgery [72,74].…”
Section: Menopausementioning
confidence: 99%
“…Being the result of prolonged heavy periods, chronic pelvic pain, and severe MRD, depressed mood is, however, also observed in women before hysterectomy [71][72][73][74]. Hysterectomy may thus improve mood, except for women with preexisting psychiatric illness or predisposing personality problems, in whom depressed mood may persist or re-occur in response to the stress associated with surgery [72,74]. Finally, thirty eight percent of women experiencing induced menopause due to treatment of breast cancer have been observed to develop major depression and 95% dysphoria within the first 6 months of treatment [75].…”
Section: Menopausementioning
confidence: 99%
“…Later studies have not been able to confirm this finding [2][3][4], On the con trary, a careful prospective study [4] revealed that overall levels of psychiatric morbidity were significantly reduced after hysterectomy. However, women with a preoperative psychiatric morbidity run an increased risk of developing a depression postoperatively [4,5], In a study by Martin [6], higher levels of psychiatric morbidity were found amongst women awaiting hysterectomy compared to a control group. Previous studies regarding hysterectomy and possible effects on sexual life are inconsistent reporting conflicting results [2,4,[7][8][9], Symptoms such as fatigue and headache were more often found in women in whom an oophorectomy had been performed [6], When the ovaries were preserved, sexual life was unaffected or improved after hysterectomy [2,4], When hysterectomy was combined with oophorec tomy, a negative influence on sexual life was reported [9,10] and estrogen replacement therapy did not seem to improve the libido in this group [9], However, most of the previous studies rely on rather small materials often with only a short period of postoperative observation.…”
Section: Introductionmentioning
confidence: 99%
“…Aunque, las mujeres con patología psiquiátrica previa a la cirugía tienen más riesgo de desarrollar depresión tras la misma 23,25 .…”
unclassified